Pengaruh Latihan Pliometrik Depth Jump dan Knee Tuck Jump Terhadap Hasil Tendangan Lambung Atlit Sepak Bola Pemula di SMP Al-Firdaus Surakarta (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2009)
Sport is physical activity has competitive in a game one of them football, one of them that influence success power leg, be federation from muscle strength and speed so that produce energy and kick lambung. Practice existence pliometrik depth jump and knee tuck jump in enhanced power pass adaptation in muscle spindle and unit motor in leg muscle. This research method appearance experiment watchfulness is done in football team beginner athlete at SMP Al-Firdaus surakarta with sample taking 32 aged athletes 12 - 15 year. This sample is divided to be two groups that is group depth jump and group knee tuck jump, data taking technique is done with watchfulness design pre - post test two group use practice pliometrik depth jump and knee tuck jump with data analysis with test t-tes and done measurement by using measuring instrument rollmeter in meter unit. Research done during 6 weeks thatÂ  July until August. Analysis result to normalitas data pre-test depth jump and knee tuck jump with test kolmogorov smirnov p=0,478. Group treatment dept jump before and after, paired t-test value p= 0,000. Group knee tuck jump before and after, paired t-test value p=0,000. Difference pos-test group dept jump and knee tuck jump, independent t-test value influence p=0,004. This watchfulness conclusion demoes that practice pliometrik knee tuck jump more give influence towards kick result.keywords: Plyometrics, MWD, Power Leg